Diseño e implementación de una estación de monitoreo de variables agroclimáticas para cultivos durante temporadas de sequías prolongadas en la región caribe colombiana (2020)
The present proposal seeks to develop a monitoring station for the variables of humidity level and soil temperature, temperature and humidity of the environment and level of solar radiation to be used in the programming of agricultural crop irrigation during prolonged drought seasons. The proposed system will be able to store, visualize and send the data remotely through the GSM network. Likewise, the system will be able to receive requests to send data from smart devices. The monitoring station will operate in the field, amid agricultural crops and will be powered by photovoltaic energy.